2022
DOI: 10.3390/su14063352
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Streamflow Forecasting Using Hybrid Deep Learning Model Based on Grey Wolf Algorithm for Hydrological Time Series

Abstract: The effects of developing technology and rapid population growth on the environment have been expanding gradually. Particularly, the growth in water consumption has revealed the necessity of water management. In this sense, accurate flow estimation is important to water management. Therefore, in this study, a grey wolf algorithm (GWO)-based gated recurrent unit (GRU) hybrid model is proposed for streamflow forecasting. In the study, daily flow data of Üçtepe and Tuzla flow observation stations located in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…The authors showed the advantages of the hybridization based on DL algorithms, achieving accurate predictions with R 2 values up to 0.98. The results obtained by Kilinc and Yurtsever 40 are in line with the prediction obtained for several rivers investigated in the present study for t = 1 day. However, they did not perform an analysis with increasing time horizon, as made in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The authors showed the advantages of the hybridization based on DL algorithms, achieving accurate predictions with R 2 values up to 0.98. The results obtained by Kilinc and Yurtsever 40 are in line with the prediction obtained for several rivers investigated in the present study for t = 1 day. However, they did not perform an analysis with increasing time horizon, as made in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The authors calculated values of NSE up to 0.48, also showing a performance reduction as the forecast horizon increased, as observed in the present study. Kilinc and Yurtsever 40 also developed a hybrid DL model Based on Grey Wolf algorithm (GWO) and GRU for the daily streamflow forecasting in two stations located in the Seyhan basin, Turkey. The authors showed the advantages of the hybridization based on DL algorithms, achieving accurate predictions with R 2 values up to 0.98.…”
Section: Discussionmentioning
confidence: 99%
“…The deep learning hybrid model, known as the gray wolf algorithm (GWO)-based recurrent gated unit (GRU) (GWO-GRU), was developed by 42 for forecasting daily flow rates, utilizing its antecedents as input variables. The proposed model was compared with a linear model.…”
Section: Introductionmentioning
confidence: 99%
“…Streamflow forecasting plays an important role in water resources planning and management in both the short and long term [1,2]. Accordingly, developing a precise and reliable model for streamflow forecasting is of high significance [3].…”
Section: Introductionmentioning
confidence: 99%